2020
DOI: 10.1002/cctc.201902033
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Transfer Hydrogenation of Furfural over Co3O4−Al2O3 Hydrotalcite‐derived Catalyst

Abstract: The hydrogenation of furfural by catalytic hydrogen transfer to produce furfuryl alcohol has been investigated over a series of mixed oxides derived from hydrotalcite catalysts. Three different catalysts containing Ni, Co and Zn phases on an Al‐rich amorphous support were synthesized and characterised. The catalytic performances were evaluated in a batch stirred reactor using 2‐propanol as a solvent and hydrogen donor, with Co3O4−Al2O3 showing the highest activity and selectivity to FA (74 % yield; 97 % select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…The use of alcohols as hydrogen donors in catalytic transfer hydrogenation (CTH) has been extensively investigated in which 2-propanol has been identified as the most promising candidate ( Li et al., 2016b , 2020 ; Panagiotopoulou et al., 2014 ; He et al., 2018 ; Ramos et al., 2020 ; Fan et al., 2021 ). Using the silicalite-1 confined ultrasmall CuO (3CuO@sil-1) as the catalyst, we also investigated the effects of different alcohols including methanol, ethanol, and 2-propanol as the hydrogen donor on the CTH of FAL.…”
Section: Resultsmentioning
confidence: 99%
“…The use of alcohols as hydrogen donors in catalytic transfer hydrogenation (CTH) has been extensively investigated in which 2-propanol has been identified as the most promising candidate ( Li et al., 2016b , 2020 ; Panagiotopoulou et al., 2014 ; He et al., 2018 ; Ramos et al., 2020 ; Fan et al., 2021 ). Using the silicalite-1 confined ultrasmall CuO (3CuO@sil-1) as the catalyst, we also investigated the effects of different alcohols including methanol, ethanol, and 2-propanol as the hydrogen donor on the CTH of FAL.…”
Section: Resultsmentioning
confidence: 99%
“…Hf-TUD-1(x) catalysts are the first Hf-mesoporous silicates reported for Fur conversion using secROH. The catalytic results for Hf-TUD-1(x) were compared with literature data for fully inorganic heterogeneous non-noble metal catalysts tested for Fur conversion to AMFs in alcohol medium ( Table 2 ) [ 34 , 36 , 37 , 39 , 42 , 43 , 61 , 62 , 65 , 67 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. The present work does not concern noble metal catalysts for Fur conversion, which may be found in a vast literature such as the following references, just to cite a few [ 86 , 87 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas, in the presence of an equimolar concentration of benzoic acid, hardly any FUR conversion was observed. Freire and coworkers synthesized NiO−Al 2 O 3 , Co 3 O 4 −Al 2 O 3 , and ZnAl 2 O 4 −Al 2 O 3 catalysts by calcining their respective hydrotalcite precursors at 500 °C for 5 h in air [31] . Among these catalysts, Co 3 O 4 −Al 2 O 3 exhibited the highest activity with 76 % FUR conversion and 74 % FOL yield at 150 °C using 2‐propanol as H‐donor solvent (Table 4).…”
Section: Furfuryl Alcohol (Fol)mentioning
confidence: 99%
“…catalysts for the transfer hydrogenation of FUR. [31] Acid content (L/B) [ Yang and coworkers synthesized AlÀ Zr@Fe O catalysts with a magnetic core and employed them for the transfer hydrogenation of FUR at 180°C using 2-propanol as H-donor solvent. [33] Al 7 Zr 3 @Fe 3 O 4 (1/1) catalyst afforded 99 % FUR conversion and 90 % FOL yield in 4 h. The recyclability test indicated that the catalyst could be easily recovered by applying a magnet, and the catalytic activity decreased slightly in the 5 th catalytic cycle with 96 % FUR conversion and 84 % FOL yield.…”
Section: Transfer Hydrogenation Of Fur To Fol Using Alcohol As H-donorsmentioning
confidence: 99%